Wacana Pemerintahan Demoktis dan Dinamika Politik di Negeri-negeri Timur Tengah: Saudi Arabia, Yordania, Mesir, Iran, dan Turki - Muhammad Turhan Yani (Islamica: Jurnal Studi Keislaman, 2007)
Democracy -which means an authority of the people as opposed to that of theruler- fair general election, civil supremacy, equality before law, and governmentaccountability are seemingly inapplicable in Arab countries. Applying democracy andsustaining it will require what Bernard Lewis calls ?gradual and deliberate change?, whichwill take these countries to a reform process from a political autocracy to an open andcompetitive political system. The same view is echoed by Robin Wright. To him, democracyin Arab countries will need a long time to take place. This is because culturally andsocially speaking political freedom and individual participation in politics are hard tocome by in these countries.